THE EFFECT OF GOOD CORPORATE GOVERNANCE, AUDIT COMMITTEE COMPOSITION, AND WHISTLEBLOWING SYSTEM ON FRAUD DISCLOSURE - Agerta, Maya Tiara; Wahyudi, Ilham; Olimsar, Fredy (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
This study aims to investigate how fraud disclosure is influenced by good corporate governance, the audit committees' composition, and the whistleblowing system in financial sector companies. The rationale behind the selection of financial sector corporations is the high disclosure rate of fraud cases in this industry, which includes businesses that play a significant role in the economy and govern the financial sector in society. The Indonesia Stock Exchange's official website provides the secondary data for this quantitative analysis, which employs a purposive sampling strategy. With the aid of Statistical Product Service Solution (SPSS) version 29, ordinal logistic regression tests were used to analyze the data. The findings show that while whistleblowing systems have a favorable effect on fraud disclosure, sound corporate governance and the makeup of audit committees have no effect on it.